Studije o fenomenu zla u sociološkom diskursu A. J. Vetlesena / The Study of Evil as a Phenomenon in A. j Vetlesen's Sociological Discourse - Bečirović, Fikret (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
This text is a review of a book Evil and Human Agency by Arne Johan Vetlesen, University of Sarajevo Institute for Research of Crimes against Humanity and International Law, Sarajevo, 2017.